A Case Report on Application of Multimodal Imaging to an Alcoholic Cardiomyopathic Patient Undergoing Heart Transplantation - Zhiming Li; Yu Wang; Bingsong Duan; Dan Han; Wei Chen (Cardiology Discovery)
Alcoholic cardiomyopathy (ACM) is a dilated cardiomyopathy induced by excessive alcohol consumption that causes progressive cardiac dysfunction and chamber dilatation, leading to arrhythmias, heart failure, and death. Cardiac transplantation is the final measure for end-stage ACM. In this case, we used multimodal imaging for ACM diagnosis in a patient with refractory heart failure. The patient received a heart transplant with a good prognosis, and his pathological results after the transplant confirmed our suspected diagnosis. End-stage ACM may lead to refractory heart failure and multimodal imaging may play an important role in the diagnosis, prognosis prediction, and follow-up study of suspected ACM.